Umrah Manasik Guidance Strategy At Zafa Tour Bengkulu To Increase Congregation Understanding - Nabila, Tasya; Setiawan, Romi Adetio; Setiawan, Adi (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
This community service aims to find out how Zafa Tour Bengkulu's strategy is to increase understanding of the congregation. Ensuring the congregation's understanding is in accordance with the Shari'a is an important task for PT. Zafa Mulia Mandiri, even for all other travelers. However, before going into the strategy itself further, there are several things that Zafa Tour Bengkulu must pay attention to. The methods used in this service activity are lecture methods, question and answer sessions and simulations in the form of practice accompanied by demonstrations by the presenters, the congregation present and the entire committee. Through this ritual activity, the congregation shows increased understanding through being active during the activity and briefly summarizing the insights gained. However, even though rituals are regularly held, regular evaluations and various teaching innovations may be needed so that learning is memorable and well received by the congregation.